2021
DOI: 10.1111/cts.13124
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic polygenic risk score for clopidogrel responsiveness among Caribbean Hispanics: A candidate gene approach

Abstract: This multicenter clinical study was aimed at conducting a targeted pharmacogenomic association analysis of residual on‐clopidogrel platelet reactivity in 474 Caribbean Hispanic patients. Platelet reactivity was measured using the VerifyNow P2Y12 assay and clopidogrel resistance was defined as P2Y12 reaction units (PRUs) greater than or equal to 208. Genotyping was performed using the whole‐genome Infinium MEGA BeadChip array. An ancestry‐adjusted, weighted polygenic risk score (wPGxRS) was developed to account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…lacking. A notable exception is a recent study conducted in an admixed population of 474 Caribbean Hispanic ACS/PCI patients treated with clopidogrel across multiple sites in Puerto Rico (68). The average European, Native American, and African ancestry genomic proportions in the study population were 70, 11, and 19%, respectively.…”
Section: Racial and Ethnic Disparities In Discovery Studies That Iden...mentioning
confidence: 90%
See 3 more Smart Citations
“…lacking. A notable exception is a recent study conducted in an admixed population of 474 Caribbean Hispanic ACS/PCI patients treated with clopidogrel across multiple sites in Puerto Rico (68). The average European, Native American, and African ancestry genomic proportions in the study population were 70, 11, and 19%, respectively.…”
Section: Racial and Ethnic Disparities In Discovery Studies That Iden...mentioning
confidence: 90%
“…Furthermore, because minority populations have been underrepresented in clopidogrel pharmacogenomics discovery studies, the presence and magnitude of effect of CYP2C19 no function alleles on antiplatelet effects and MACE risk in Black, Hispanic, and other underrepresented minority populations (e.g., Native American, Pacific Islander) remains unclear. It is possible that the effect size of these associations varies across populations and genotypes beyond CYP2C19 could be important in non-European and non-East Asian populations ( 68 , 93 ). Therefore, in the absence of outcome evidence, it may not be appropriate to assume effectiveness and generalize clinical recommendations for CYP2C19 genotype-guided antiplatelet therapy in populations that are underrepresented or excluded from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, genetic variants of SLCO1B1 rs113681054, SLCO1B1*5 (rs4149056), and CYP3A5*3 (rs776746) were also reported to have no relevance in the PK of ticagrelor in healthy Chinese volunteers (Li et al, 2017a). Platelet endothelial aggregation receptor (PEAR1; location: 1q23.1) plays a vital role in platelet adhesion and platelet aggregation via sustaining αIIbβ3 activation (Duconge et al, 2021). Prior studies have confirmed that PEAR1 triggers PI3K/AKT/PTEN signaling, which leads to megakaryopoiesis and neoangiogenesis (Kauskot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%